Short‐and long‐run determinants of sovereign debt credit ratings - Afonso, António (2022)
We study the determinants of sovereign debt ratings from the three main rating agencies, for the period 1995–2005. Using linear and ordered response models, we employ a specification that allows us to distinguish between short- and long-run effects, on a country’s rating, of macroeconomic and fiscal variables. Changes in GDP per capita, GDP growth, government debt, and government balance have a short-run impact on a country’s credit rating, while government effectiveness, external debt, foreign reserves, and default history are important long-run determinants.